Integrated Administrative Service Quality In Bantan District Bengkalis Regency (Study Of E-KTP Management) - Ahmad Fitra Yuza; Handoko Putra (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2023)
District Integrated Services provides e-KTP Management services. Districts play a roles in providing satisfactionto recipients of e-KTP management services However, in reality there are still many people who are still not satisfied with the achievement of the completion time for the services provided. The purpose of this study was to determine the Qualityof Integrated Administration Services in Bantan District, Bengkalis Regency (E-KTP Management Study) and to determine the inhibiting factors of the Integrated Administration Service Quality in Bantan District, Bengkalis Regency (E-KTP Management). learn). The research method used is a quantitative method with data collections techniquesthrough observation, questionnaires, interviews and documentation. Discussion on the Quality of IntegratedAdministrative Services in Bantan regency, Bengkalis regency in the management of E-KTP has not been implementedbased on standards operating procedures. so that it has not provided satisfactory achievements for the community.Conclusion the Quality of Integrated Administrative Services in Bantan regency, Bengkalis Regency in the managementof E-KTP has been implemented but has not been implemented optimally in accordance with Standard Operating Procedures starting from the completion of the time for making E-KTP. This is due to a lack of personnel and supporting infrastructure in providing services. Researcher's suggestion is that Kelurahan Officers in managing E-KTP should increase the number of officers in providing services and cooperate with officers and provide service support facilities in order to achieve maximum service.